Abnormal steroid excretion in gestational trophoblastic disease complicated by ovarian theca-lutein cysts. Issue 6 (June 1986) - Bevan, B R; Savvas, M; Jenkins, J M; Baker, K; Pennington, G W; Taylor, N F
Abstract : Serum and urine steroids were examined in two subjects with trophoblastic disease accompanied by large ovarian theca-lutein cysts and compared with those from 10 patients with trophoblastic disease but without palpable cysts. In the patients without cysts normal values were obtained for serum oestradiol, progesterone, 17 alpha-hydroxyprogesterone and androstenedione, and for urinary total oestrogens, pregnanediol, pregnanetriol, and 17-oxosteroids. Nineteen urinary steroid metabolites, quantified by capillary gas-liquid chromatography, were either within reference limits or marginally raised. In several cases relatively minor increases in serum testosterone and cortisol and urinary free cortisol were observed. In contrast, the subjects with cysts showed pronounced excesses of androgen metabolites, 17 alpha-hydroxypregnenolone, pregnanediol, and pregnanetriol, and both exhibited a similar pattern of unusual additional metabolites. The profiles superficially resembled those seen in 21-hydroxylase deficiency adrenogenital syndrome, but there were important discrepancies reflecting known differences in ovarian and adrenal steroid metabolism. Chemotherapy led to decline of human chorionic gonadotrophin concentrations, regression of the cysts, and return to normal of the steroid profile. Excess steroids in the patients with cysts may have originated in the ovary rather than in the trophoblastic tissue.